From The Corner To The Office: An Analysis Of The Absence Of Transgender Women In The Formal Labor Market In Goias - Rodrigues Gonçalves, João Vitor; Simancas Trujillo, Ricardo Antonio; Rodrigues Gonçalves, João Vitor; Simancas Trujillo, Ricardo Antonio; Rodrigues Gonçalves, João Vitor; Simancas Trujillo, Ricardo Antonio (Corporación Universitaria Americana, 2020)
The aim of this study is to analyze the absence of transsexual women in organizations, based on testimonials that seek to combine the existing relationship between transsexuals and the working world in Goiás. The intention was to give visibility to the main difficulties encountered by transsexuals when trying to enter into the market, in order to contribute to the discussion about alternatives that may promote their insertion. The results indicate that the lack of public policies and the unpreparedness of companies are considered the determining factors that reaffirm their exclusion in the labor market. The methodological approach focuses on literature review and document analysis. As a result of COVID-19, the testimonials were built in a virtual way, using active technologies. In summary, it is necessary to propose actions that ensure the participation of transsexuals from the elaboration to the implementation of business strategies and public policies that could help and guarantee the insertion of transsexual women in the market.